Forecasting without Consequence? Evidence on the Properties of Retiring CEOs' Forecasts of Future Earnings - Cassell, Cory A.; Huang, Shawn X.; Sanchez, Juan Manuel (The Accounting Review, 2013)
ABSTRACT: We investigate whether retiring CEOs engage in opportunistic terminal-year forecasting behavior and the circumstances in which such behavior is likely to be more or less pronounced. Using a within-CEO empirical design, we find that retiring CEOs are more likely to issue forecasts of future earnings, and that they issue such forecasts more frequently in their terminal year relative to other years during their tenure with the firm. Further, retiring CEOs' terminal-year forecasts of future earnings are more likely to convey good news and are more optimistically biased relative to pre-terminal years. Opportunistic terminal-year forecasting behavior is: (1) more pronounced in the presence of higher CEO equity incentives and when discretionary expenditures are cut in the terminal year, and (2) less pronounced in the presence of stronger monitoring mechanisms, such as higher institutional ownership. Collectively, our results provide evidence on a potential implication of the CEO horizon problem that has not been investigated previously. Data Availability: All data used in the study are publicly available from the sources cited in the text.